HBV Infection Status and the Risk of Cholangiocarcinoma in Asia: A Meta-Analysis. (23rd November 2016) - Zhang, Hao; Zhu, Biqing; Zhang, He; Liang, Jianxin; Zeng, Wenting
Abstract : Background . The inconsistent finding was between hepatitis B virus (HBV) infections and cholangiocarcinoma (CCA). This meta-analysis is to explore this relationship in Asia. Methods . A literature search was performed using PubMed, Web of Science, and Cochrane Library to October 30, 2015. Pooled incidence rate and OR with 95% CI were calculated using STATA 11.0. Results . Thirty-nine studies were included. The pooled incidence rate of CCA patients with HBV infection was 31% (95% CI 22%–39%). The pooled OR showed increased risk of CCA incidence with HBV infection (OR = 2.72, 95% CI 1.90–3.88), especially in ICC (OR = 3.184, 95% CI 2.356–4.302), while it showed no risk in ECC (OR = 1.407, 95% CI 0.925–2.141). Also, the pooled OR showed increased risk of ICC and ECC incidence (OR = 6.857, 95% CI 4.421–10.633 and OR = 1.740, 95% CI 1.260–2.404) in patients with HBsAg+/HBcAb+. The pooled OR showed increased risk of ICC incidence (OR = 1.410, 95% CI 1.095–1.816) in patients with HBsAg−/HBcAb+. Conclusion . It is suggested that HBV infection is associated with an increased risk of CCA in Asia. Two HBV infection models (HBsAg+/HBcAb+ and HBsAg−/HBcAb+) increase the risk of CCA, and patients with HBsAg−/HBcAb+ also had a risk of ICC. This trial is registered with PROSPERO CRD42015029264 .